A new approach to the synthesis of nanocrystal conjugated polymer composites - Watt, A; Rubinsztein-Dunlop, H; Meredith, P (2005)
A novel one pot process has been developed for the preparation of PbS nanocrystals in the conjugated polymer poly 2-methoxy, 5-(2 - ethyl-hexyloxy-p-phenylenevinylene) (MEH-PPV). Current techniques for making such composite materials rely upon synthesizing the nanocrystals and conducting polymer separately, and subsequently mixing them. This multi-step technique has two serious drawbacks: templating surfactant must be removed before mixing, and co-solvent incompatibility causes aggregation. In our method, we eliminate the need for an initial surfactant by using the conducting polymer to terminate and template nanocrystal growth. Additionally, the final product is soluble in a single solvent. We present materials analysis which shows PbS nanocrystals can be grown directly in a conducting polymer, the resulting composite is highly ordered and nanocrystal size can be controlled. © 2005 Elsevier B.V. All rights reserved.